Mediastinal Kaposiform Hemangioendothelioma and Kasabach-Merritt Phenomenon in a Patient with no Skin Changes and a Normal Chest CT. (1st September 2014) - Wallenstein, Matthew B.; Hole, Michael K.; McCarthy, Chad; Fijalkowski, Natalia; Jeng, Michael; Wong, Wendy B.
<x xml:space="preserve">Abstract</x> A 16-month-old previously healthy boy was admitted to the hospital with respiratory distress and thrombocytopenia. Initial workup demonstrated large pleural and pericardial effusions. The patient had no cutaneous abnormality on physical examination, and his initial chest CT (computed tomography) was nondiagnostic. He required multiple platelet transfusions, chest tube placement, and pericardiocentesis. Sixteen days after admission, a chest MRI (magnetic resonance imaging) revealed a large infiltrative mass of the superior mediastinum, consistent with kaposiform hemangioendothelioma (KHE). The patient's thrombocytopenia was due to associated Kasabach-Merritt phenomenon (KMP). The patient now has complete resolution of KMP after medical treatment with prednisolone, aminocaproic acid, vincristine, and aspirin.